2018
DOI: 10.1007/978-3-319-95972-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Optimisation of Neural Network Models for Fish Collective Behaviours in Mixed Groups of Robots and Zebrafish

Abstract: Animal and robot social interactions are interesting both for ethological studies and robotics. On the one hand, the robots can be tools and models to analyse animal collective behaviours, on the other hand the robots and their artificial intelligence are directly confronted and compared to the natural animal collective intelligence. The first step is to design robots and their behavioural controllers that are capable of socially interact with animals. Designing such behavioural bio-mimetic controllers remains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Namely, small circular loops can appear in all simulated cases (especially here with NSGA-III cases) when simulated agents performs U-turns to catch up with the rest of the group. Previous analyses in 36 showed that this effect cannot be easily mitigated even when the fitness function takes into account agents angular speeds.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Namely, small circular loops can appear in all simulated cases (especially here with NSGA-III cases) when simulated agents performs U-turns to catch up with the rest of the group. Previous analyses in 36 showed that this effect cannot be easily mitigated even when the fitness function takes into account agents angular speeds.…”
Section: Resultsmentioning
confidence: 98%
“…makes them suitable to model control problems 39 . We consider MLP with only one hidden layer of 100 neurons (using a hyperbolic tangent function as activation function) as in 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations